Μicro-structured tungsten: an advanced plasma-facing material. (May 2019) - Terra, A.; Sergienko, G.; Tokar, M.; Borodin, D.; Dittmar, T.; Huber, A.; Kreter, A.; Martynova, Y.; Möller, S.; Rasiński, M.; Wirtz, M.; Loewenhoff, Th.; et al.
Highlights: Improving tungsten thermal cycling handling capabilities and reducing cracks occurring as plasma facing material (PFM). Development of new structured tungsten at micron scale. Testing and evaluation of its performances as a PFM. Abstract: A micro-structuring of the tungsten plasma-facing surface can strongly reduce near surface thermal stresses induced by ELM heat fluxes. This approach has been confirmed by numerical simulations with the help of ANSYS software. For experimental tests, two 10 × 10 mm 2 samples of micro-structured tungsten were manufactured. These consisted of 2000 and 5000 vertically packed tungsten fibres with dimensions of Ø240 µm × 2.4 mm and Ø150 µm × 2.4 mm, respectively. The 1.2 mm bottom parts of the fibres are embedded in a copper matrix. The top parts of the fibres have gaps about of 10 µm so they are not touching each others. The top of all tungsten fibres was electro-polished. A Nd:YAG laser with a pulse duration 1 ms and a pulse repetition frequency of 25 Hz was used to simulate up to 10 5 ELM-like heat pulses. No damage on either of the micro-structured tungsten samples were observed. Neon plasma erosion rate and fuel retention of the micro-structured tungsten samples were almost identical to bulk tungsten samples.